„Urgent” menopausal problem - Nowara, Adam; Witek, Andrzej (Menopause Review/Przegląd Menopauzalny, 2007)
Overactive bladder (OAB) is characterized by urinary urgency, pollakiuria, nocturia and urge incontinence with urgency but with a lack of local factors that could explain the occurrence of such troubles. These symptoms have a material impact on the quality of life of millions of women worldwide. Frequency of overactive bladder in adults is estimated at approximately 16%. The symptoms of overactive bladder are associated with considerable social, psychological, professional, physical and sexual problems. This paper is a review of current information about the definition, epidemiology, pathogenesis, diagnostics and treatment of overactive bladder.